Comparative study of the effect of solvents on the efficacy of neonicotinoid insecticides against malaria vector populations across Africa - Magellan Tchouakui; Tatiane Assatse; Leon M. J. Mugenzi; Benjamin D. Menze; Daniel Nguiffo-Nguete; Williams Tchapga; Jonathan Kayondo; Francis Watsenga; Emile Zola Manzambi; Michael Osae; Charles S. Wondji (BMC, 2022)
Abstract Background New insecticides with a novel mode of action such as neonicotinoids have recently been recommended for public health by WHO. Resistance monitoring of such novel insecticides requires a robust protocol to monitor the development of resistance in natural populations. In this study, we comparatively used three different solvents to assess the susceptibility of malaria vectors to neonicotinoids across Africa. Methods Mosquitoes were collected from May to July 2021 from three agricultural settings in Cameroon (Njombe-Penja, Nkolondom, and Mangoum), the Democratic Republic of Congo (Ndjili-Brasserie), Ghana (Obuasi), and Uganda (Mayuge). Using the CDC bottle test, we compared the effect of three different solvents (ethanol, acetone, MERO) on the efficacy of neonicotinoids against Anopheles gambiae s.l. In addition, TaqMan assays were used to genotype key pyrethroid-resistant markers in An. gambiae and odds ratio based on Fisher exact test were used to evaluate potential cross-resistance between pyrethroids and clothianidin. Results Lower mortality was observed when using absolute ethanol or acetone alone as solvent for clothianidin (11.4‒51.9% mortality in Nkolondom, 31.7‒48.2% in Mangoum, 34.6‒56.1% in Mayuge, 39.4‒45.6% in Obuasi, 83.7‒89.3% in Congo and 71.1‒95.9% in Njombe pendja) compared to acetone + MERO for which 100% mortality were observed for all the populations. Similar observations were done for imidacloprid and acetamiprid. Synergist assays (PBO, DEM and DEF) with clothianidin revealed a significant increase of mortality suggesting that metabolic resistance mechanisms are contributing to the reduced susceptibility. A negative association was observed between the L1014F-kdr mutation and clothianidin resistance with a greater frequency of homozygote resistant mosquitoes among the dead than among survivors (OR = 0.5; P = 0.02). However, the I114T-GSTe2 was in contrast significantly associated with a greater ability to survive clothianidin with a higher frequency of homozygote resistant among survivors than other genotypes (OR = 2.10; P = 0.013). Conclusions This study revealed a contrasted susceptibility pattern depending on the solvents with ethanol/acetone resulting to lower mortality, thus possibly overestimating resistance, whereas the MERO consistently showed a greater efficacy of neonicotinoids but it could prevent to detect early resistance development. Therefore, we recommend monitoring the susceptibility using both acetone alone and acetone + MERO (4 µg/ml for clothianidin) to capture the accurate resistance profile of the mosquito populations. Graphical Abstract